Study about Utilization of Used Oil by Ceramic Membrane - Muhammad Hatta Dahlan (Sriwijaya International Seminar on Energy-Environmental Science and Technology, 2014)
High quantity of vehicle use have been triggered to increase the use of oil and caused the increase of used oil in environment. Used oil might contained the metallic elements such as aluminum (Al), iron (Fe), copper (Cu) and zinc (Zn). In this study, ceramic membrane was used to separate the metal elements to utilize the used oil. The objective of this research were to investigate the metal separation process from used oil and to analyze the effect of metal separation by using ceramic membrane. The materials that used as membrane component were zeolite, iron powder and clay. Flux analysis showed that ceramic membrane which contain 30% zeolit, 5% iron powder and 65% clay at flowrate 3L/min were resulted in Al 0.12 ppm, 0.12 ppm Fe, Cu 0.003 ppm and Zn 0.07 ppm .